Enzymatic synthesis of biobased poly(1, 4-butylene succinate-ran-2, 3-butylene succinate) copolyesters and characterization. Influence of 1, 4- and 2, 3-butanediol contents. (August 2017) - Debuissy, Thibaud; Pollet, Eric; Avérous, Luc
Graphical abstract: Highlights: Enzymatic synthesis of copolyesters with high 2, 3-butanediol unit content. Optically active copolyesters based on 2, 3-butanediol content. Copolyesters with excellent thermal stability until 250 °C. From semi-crystalline to fully amorphous copolyesters increasing 2, 3-butanediol contents. Modulation of the glass transition temperature with the 2, 3-butanediol content. Abstract: Different (co)polyesters, poly(1, 4-butylene succinate- ran -2, 3-butylene succinate) (PBB'S), were enzymatically copolymerized at different 1, 4-butanediol (1, 4-BDO)/2, 3-butanediol (2, 3-BDO) molar ratios, with immobilized Candida antarctica lipase B (CALB). The synthesized macromolecular architectures were characterized by NMR, SEC, FTIR, WAXS, MALDI-TOF MS, DSC, TGA and specific optical rotation. Based on an optimized process, PBB'S copolyesters were synthesized in high yield. A random distribution between both BDOs was obtained along the chain. M w ‾ decreased with increasing 2, 3-BDO content, from 26 to 6 kg/mol. The specific optical rotation decreased linearly with decreasing 2, 3-BDO content, and can be used as a characterization technique to determine PBB'S composition. DSC results showed that an increase in 2, 3-BDO content raised the Tg and reduced the degree of crystallinity, leading to amorphous materials for 2, 3-BDO content higher than 47 mol.%. Synthesized copolyesters exhibited a good thermal stability, higher than 250 °C, with a degradation profile depending on the 1, 4-BDO/2, 3-BDO ratio.